Biliteracy Learners’ Enacted Agency in Digital Storytelling: Creativity in a Cross-Border, Online, Emergent, Biliteracy Curriculum - Zhang, Zheng; Li, Wanjing (Journal of the Canadian Association for Curriculum Studies, 2020)
This research investigated potentials of bilingual digital story-making for engaging creativity in Canadian biliteracy learners (i.e., learners in Canada who speak their heritage language of Mandarin but are more fluent in English) and Chinese biliteracy learners (i.e., learners in China who are fluent in Mandarin and learning English as a foreign language). Informed by asset-oriented multiliteracies, new media literacies and new materialism, this research adopted an ethnography methodology to explore the communal and socio-material practices embedded in the intra-actions of human, matter and virtual spaces of Seesaw and Skype. Drawing on various data about six focal students, findings show how the intra-actions among researchers, teachers, students, materials and spaces shaped the participants’ creative acts. This research adds to the literature about developing and applying pedagogies that attend to the enacted agency among teachers, students, materials and spaces in processes of creative meaning making.